Role of Lymphangiogenesis in Cardiac Repair and Regeneration - Zhongyun Xu; Qing Lu; Liming Chen; Chengchao Ruan; Yingnan Bai; Yunzeng Zou; Junbo Ge (Methodist DeBakey Cardiovascular Journal)
This article highlights the importance of the structure and function of cardiac lymphatics in cardiovascular diseases and the therapeutic potential of cardiac lymphangiogenesis. Specifically, we explore the innate lymphangiogenic response to damaged cardiac tissue or cardiac injury, derive key findings from regenerative models demonstrating how robust lymphangiogenic responses can be supported to improve cardiac function, and introduce an approach to imaging the structure and function of cardiac lymphatics.